The attitude and psychological status of medical staff in China during the COVID-19 outbreak: a cross-sectional survey - Yan, Ziyi (Lancet, 2020)
BACKGROUND: In early 2020, the outbreak of coronavirus disease 2019 (COVID-19) in China greatly increased the burden on medical staff. We aimed to investigate the attitudes of medical practitioners towards arranging rotations for medical students during this period of staff shortage and to assess their psychological state. METHODS: We used the self-rating depression scale (SDS) and the self-rating anxiety scale (SAS) to do a psychological assessment of both medical and non-medical staff from 25 centres in different provinces in China. Participants were recruited through hospital departments, online medical-alumni organisations, and open recruitment through online platforms. Participant eligibility criteria for all participants included being older than 18 years and living in China during the survey period, and participant-specific criteria included the following: medical practitioners had to work as a doctor, nurse, or clinical laboratory technician in a medical institution, and work during the COVID-19 outbreak; medical students had to have majored in clinical medicine, nursing, or clinical laboratory diagnosis, and be on an undergraduate internship (phase 1 student) or postgraduate or standardised trainees (phase 2 student), and had to work during the COVID-19 outbreak; non-medical participants had to work in non-medical industries. Medical staff included medical practitioners and medical students. We used WeChat online questionnaires to investigate the attitude of medical practitioners and medical students to arranging for students to be on duty during the epidemic period. The primary outcomes of this study were attitude of medical staff to medical students, depression index (according to the SDS), and anxiety index (according to the SAS). We used descriptive statistics to analyse demographic covariates, SDS scores, and SAS scores, χ(2) and Fisher's exact test to compare categorical data, independent t-tests and one-way ANOVA tests to compare numerical data, LSD tests and Tamhane tests to compare significance in multiple groups, Pearson's tests to compare the goodness of fit of numerical data, and Spearman's tests to compare the goodness of fit of two ordinal category data. This study was approved by the medical ethics committee of West China Second University Hospital, Sichuan University (approval number 2020-012). The study was done in accordance with the Declaration of Helsinki and all participants provided informed consent. FINDINGS: We recruited 506 people (236 medical staff, of which 150 medical practitioners and 86 medical students, and 270 non-medical staff; 130 [26%] men and 376 [74%] women, median age 36 years, IQR 27–45) into our cross-sectional survey. 133 (56%) of 236 medical staff had a positive attitude towards arranging rotations of students on duty, with the most positive being students in phase 2 (34 [68%] of 50 had a positive attitude) and the most negative being senior practitioners (28 [40%] of 70 had a positive attitude). 178 (75%) of 236 medical staff considered students on duty to be high risk, and students in phase 1 (32 [86%] of 37) and senior practitioners (56 [80%] of 70) were particularly worried about this. 160 (68%) of 236 medical staff considered that students who refused to be on duty were excusable, even though some junior practitioners suggested punishing them (17 [22%] of 79). There was no significant difference in SDS and SAS between medical students and medical practitioners, but depression and anxiety was significantly lower than in non-medical staff (SDS 13·69, 95% CI 12·07–15·50, vs SDS 24·20, 21·30–27·11, p=0·0010; SAS 7·54, 5·83–9·46, vs SAS 18·76, 16·22–21·80, p=0·0010). In addition, people with lower education showed a higher index of depression and anxiety than people with higher education (cut-off point for higher education was a bachelor's degree; SDS 14·06, 12·63–15·68, vs SDS 35·03, 30·89–39·09, p=0·0010; SAS 8·52, 6·81–10·34, vs SAS 25·75, 22·41–29·13, p=0·0010). INTERPRETATION: Negative psychological states were associated with lower levels of educational attainment, and people with a high education and a medical background could more clearly recognise the development of the epidemic. The more clinically experienced practitioners were, the more worried they were about risks to students. The government should enact permanent bills to guarantee personal safety and accident compensation of students who are willing to go to the front line. FUNDING: None.